Analysis of the Causes of Waste with the Lean Construction Method on the 1700 Units Apartment Algeria Project - Novika Candra Fertilia; Dian Andaka (Journal of World Conference (JWC), 2021)
The construction industry is currently experiencing various problems such as time and cost overruns. One of the causes is waste. In the construction work of the 1700 apartment unit project in Algeria, it was found that waste was found in materials, tools, and time. One of the ways to control waste is lean construction. The purpose of this study is to determine the causes that have a high influence on the presence of waste in the 1700 unit Algerian apartment project and to know the strategies to manage it through the lean construction approach. This research method was conducted with a 4-stage questionnaire. The results obtained in this study are the causes that have a high effect on the presence of waste in the 1700 apartment unit construction project in Algeria: a. Last Planner System (poor planning and scheduling), b. First Run Studies (bad weather in winter), c. 5S Process (Visual Work Place) (a place where the material is easily disturbed and unsafe, and d. Fail-safe for Quality and Safety (repair work). Strategies that can be applied: a. Last Planner System: making an appropriate master schedule and evaluation daily, b.First Run Studies: evaluating the anticipation of bad weather, and claiming lost time, c. 5S Process: grouping materials and moving materials, d. Fail-safe for Quality and Safety: conducting routine daily meetings and using appropriate repair methods .